Treatment of distillery spentwash by anaerobic filter – A water conservation approach - Ilyas, M.; Isa, M.H.; Farooqi, I.H.; Khursheed, A.; Siddiqi, R.H. (1998)
The present study deals with the treatment of distillery spentwash by anaerobic filter. It was concluded that for a properly operating anaerobic system treating spentwash, neutralization of the waste is not required as biodegradation of nitrogen containing compounds and reduction of sulphates to sulphides would generate sufficient alkalinity to buffer the system. Further, the use of treated effluent as diluent has a number of advantages over the use of tap water for the same purpose. These include conservation of fresh water and preservation of the environment, imparting greater efficiency and stability to the reactor, and allowing the system to handle higher organic loads.